PENGARUH CAPITAL INTENSITY, LEVERAGE, DAN COMPANY SIZE TERHADAP TAX AVOIDANCE - Florencia Florencia; Ngadiman Ngadiman (Jurnal Paradigma Akuntansi, 2022)
This research aims to analyze the effect of capital intensity, leverage, and company size on tax avoidance. The population in this research are manufacturing companies sector consumer goods industry listed on the Indonesia Stock Exchange for 2016–2019 period. The sampling technique in this research is purposive sampling method with secondary data with a sample of 27 companies, with an observation period of 4 years in a row, so the total is 108 samples. Data analysis method used in this research is multiple linear regression analysis. The results of this research showed that company size has a significant positive effect on tax avoidance. While capital intensity and leverage do not have a significant effect on tax avoidance.